Analysis of adaptability of oat varieties and lines by productivity elements in the conditions of Kirov region - O. A. Zhuikova; G. A. Batalova (Аграрная наука Евро-Северо-Востока, 2023)
The research was carried out in 2020-2022 in the central part of the Kirov region, under varying weather conditions. In the nursery of the competitive variety testing, 3 varieties and 8 lines of hulled oats were studied in order to analyze their adaptive ability according to the elements of the productivity structure. Varieties and lines were characterized based on the sum of the ranks of the evaluation results according to the methods of S. A. Eberhart, W. A. Rassel (1966), N. A. Plokhinsky (1961), L. A. Zhivotkov et al. (1994), A. A. Rosielle and J. Hamblin (1981). There was a direct statistically significant effect of the mass of 1000 grains, the mass of grain from the panicle, the number of grains in the panicle on the yield (r = 0.62…0.85). The formation of the elements of the productivity structure depended on the hydrothermal conditions of individual periods of vegetation (r = 0.63…0.72). The method of two-factor analysis of variance revealed that the influence of the "year" factor on the elements of the productivity structure was more significant (33.7...64.3 %) than the "grade" factor (8.5...24.6 %). There have been identified lines and varieties able to form consistently high yields in contrasting weather conditions due to certain structural elements or their combined influence. A high adaptive capacity with a minimum amount of ranks was obtained by the number of spikelets in the 41h18 line (Σranks = 17), varieties Kirovsky 2 (Σranks = 14); by the number of grains in the panicle and by the weight of grains from the panicle – line 41h18 (Σranks = 14 and 15); by the weight of 1000 grains – lines 25h18, 91h18, 41h18, 50h18, 162h15 (Σranks = 21…27), varieties Medved’ and Kirovsky 2 (Σranks = 18…22). According to the total lowest sum of ranks (71...97), the Kirovsky grade 2, promising lines 25h18 and 41h18 have been identified.